Richard Lyons: The Rise and Fall of the 14th Century English Royal Financier - O. V. Yablonskaya (Научный диалог, 2019)
The article is dedicated to Richard Lyons, a London wine merchant, royal financier and politician. The results of the analysis of documentary, narrative sources, as well as modern scientific literature are presented. Richard's activity is shown against the background of the political and socio-economic history of England in the fourteenth century. The problem of the origin of the merchant, his early activities is raised, his participation in solving the financial and economic problems of the state in the 1370s is considered. It raises the question of the death of R. Lyons during the Wat Tyler revolt in connection with the attitude of the British towards foreigners, in particular the Flemings, and the internal political struggle of the “old” and “new” patriots of London. The author dwells on the analysis of the merchant’s business interests and his property status. Particular attention is paid to the "Good Parliament", at a meeting of which the House of Commons accused the government of military failure in England, condemned corruption at court and demanded to punish those responsible, including R. Lyons. The reasonability of indictment, the degree of guilt of those convicted by the parliament are analyzed. It is shown that the arrest of the royal financier was not only the result of the offenses that took place, but also the payment for the failures in the domestic and foreign policy of the entire corrupt royal authority.